Subdermal contraceptive implant in post partum women: a prospective study in a single tertiary centre in Pahang, Malaysia: a preliminary study - Abd. Wahab, Noraziana; Mustafa, Kamarul Bahyah; Abd.Rahman, Nor Azlina; Awang, Mokhtar; MA, Norhuda (2012)
Objective: The aim of the study was to evaluate the menstrual patterns and the effects of subdermal contraceptive implant, implanon®on breast feeding in post partum women during the first six months of insertion. Materials and methods: A prospective study was conducted over a one year period, from 1st July 2010 untill 30th June 2011 at outpatient gynecology clinic, Hospital Tengku Ampuan Afzan, Pahang, Malaysia. Thirty-three post partum patients requested for implanon as contraceptive method participated in the study. All patients had implanon inserted between 4 to 10 weeks of pospartum and were follow-up after 3 months and six months after the insertion. Results: There were 33 women enrolled in the study. Mean age of the patients was 30 years (range 24-41 years). Of those, 17 patients delivered by caesarean section while 16 patients had vaginal delivery. During first visit, 57.6% had amenorrhoea, 21.2% had prolonged bleeding while the incidence of normal, and irregular bleeding were 15.1% and 6.1% respectively. In second visit, 63.6% had amenorrhoea, 6.1% had prolonged bleeding while the incidence of normal and irregular bleeding were 21.2% and 9.1% respectively. Only two patients seek medical treatment due to prolonged bleeding. 28 patients continue to breast fed their babies while 5 patients stopped breast feeding while on implanon. The majority of women expressed satisfaction to her implanon® use, only three patients were not satisfied mainly due to side-effects of prolonged or irregular bleeding. There was no removal after six months follow-up Conclusions: Implanon® is a good, well accepted long-term contraceptive method for post partum women and lactating mothers. Dissatisfaction of its use is mainly due to abnormal menstrual bleeding pattern.